Awareness of Dying Remains Relevant after Fifty Years - Tom Andrews; Alvita K. Nathaniel (Grounded Theory Review: An International Journal)
This year is the fiftieth anniversary of the publication of Awareness of Dying, one of four monographs that culminated from a six-year funded research program titled Hospital Personnel, Nursing Care and Dying Patients (Glaser, 1968). Written by Barney Glaser and Anselm Strauss, Awareness of Dying (1965) was the first published study utilizing a new, groundbreaking research method. Glaser and Strauss termed this new method grounded theory because it was based upon data that was grounded in the real-live experiences of people. In this paper, we will look back at the origin of the grounded theory method and re-examine Awareness of Dying in light of more recent research in the area.